Η πράσινη διάσταση ενός business plan : - Θεοδώρου, Σοφία-Εμμανουέλα (2012)
Sustainable energy technology with a focus on energy efficiencry and conservation is an important issue that needs to be considered during the designing of hotel facilities. This study stresses the energetic and economic benefits of the renewable energy and HVAC technologies applied in a new hotel building under a theoretical framework. The location of the building has been reviewed and further investigation on which renewable energy technology and HVAC system are better suited to that location has been conducted. The thesis simulates the installation of sustainable technology has in the initial investment and we identified the time needed for obtaining a return on the investment depending on their electrical potential and power. Additionally, we consider the actual electricity bill after the installation of the above technologies, their operation and maintenance cost, their life expectancey and the national subsidiaries from the Greek development law. The thesis argues that Crete is an optimal location for the installation of photovoltaics and passive-active solar systems due to the location's direct exposure to the sun especially during the summer months. Furthermore, we conclude that even if the initial investment is high, the investment expenses are covered in four years and from that point onwards profit is generated regularly on a yearly basis.